PM1 variability and transport conditions between an urban coastal area and a high mountain site during the cold season. (October 2015) - Nicolás, J.F.; Galindo, N.; Yubero, E.; Crespo, J.; Soler, R.
Abstract: During late autumn and winter, the western Mediterranean basin is often affected by severe pollution episodes (SPE) caused by stagnant weather conditions that produce a notable increase in particulate matter (PM) levels. The main objective of the present study is to evaluate the impact of these episodes on the variability of PM1 concentrations at an urban and a high mountain station in the western Mediterranean. At the urban site, SPEs caused increases in PM1 levels of up to 20 μg m −3 at 20:00–21:00 UTC due to a decrease in the mixing layer depth during the evening rush hour. In contrast, the highest increments at the high mountain station (∼12 μg m −3 ) were observed around midday. Since there are little anthropogenic emissions in the surroundings of the mountain station, this was most likely the result of aerosol transport from coastal urban areas and photochemical formation of secondary particles during transport. The transport of air pollutants through a complex orography occurs under specific weather conditions. Highlights: The impact of winter-time stagnant conditions on PM1 levels was studied. Measurements were made at a coastal urban area and a high altitude site in Spain. Urban PM1 increases were maxima during the evening rush hour. At the mountain site the maximum increase was registered in the early afternoon. Pollutant transport from the coast to high sites occurs under specific conditions.